George Lois the Esquire covers@MoMA - Lois, George
"From 1962 to 1972, George Lois created some of the most arresting and iconic images in the history of the magazine cover. With his uniquely uncompromising point of view, Lois exploited by the communicative power of the mass-circulated front page ti simulate minds and provoke public debate. The sensational effect these covers had on public was an obvious advantage for Esquire's circulation, but their lasting importance was that they forced Americans to confront controversial issues such as racism, feminism, religion, and the Vietnam War. These images hit the public like a punch in the face, their messages artfully communicated, with force and immediacy.